Motivasi Belajar Terhadap Hasil Belajar Siswa Di SMP Negeri 2 Pancalang - Putri, Fadhlika Mulyawati; Darwan, Darwan (Society : Jurnal Pengabdian Masyarakat, 2023)
Motivation is one of the most important factors in influencing learning and learning outcomes for students at the kindergarten, elementary and junior high school levels.  However, in learning activities, it turns out that there are still students who are less active in participating in learning during the lesson.  Students or students still look lazy to learn.  Students also do not show their expressions that are happy and not enthusiastic in following ongoing learning.  Their attention is more focused on something that is opposite them than their learning tasks such as playing games in class and others. Learning motivation has a positive relationship with the learning outcomes of a subject. Thus, learning motivation contributes greatly to the achievement of student learning outcomes. Therefore, teachers must have the ability: (First) encourage learning motivation, (Second) directing learning motivation to achieve goals in achieving the learning outcomes of a subject, and (Third) strengthen learning motivation in order to ensure the consistency of students learning actions.